ChemInform Abstract: An Efficient, Mild, Solvent‐Free, One‐Pot Three‐Component Mannich Reaction Catalyzed by (C4H12N2)2 [BiCl6]Cl·H2O. Issue 39 (September 2015) - Lu, Hongfei; Wu, Runze; Cheng, Helong; Nie, Shipeng; Tang, Yan; Gao, Yuhua; Luo, Zhibin
Abstract The reaction starts from aromatic ketones, (hetero)aryl or cycloalkyl aldehydes and primary or secondary alkyl amines or (hetero)aryl amines.